Binā al-Jumal al-Mu’aqqodah fī Riwayah “Mā Lā Nabūh Bih” ala Asāsi Nadhariyyati Tagmemic Kenneth L. Pike [Complex Sentence Construction in Novel “Mā Lā Nabūh Bih” Based on the Perspective of Kenneth L. Pike’s Tagmemic] - Basid, Abdul; Syafina, Hanna Izzah; Hayati, Husnizan; Nazir, Husni; Razi, Fakhrur (Center of Language Development, Institut Agama Islam Negeri Madura, 2022)
Sentence studies that are rarely discussed in the realm of linguistics are complex sentences. This article aims to describe the construction and types of complex sentences based on their clause formation in the novel Mā Lā Nabūh Bih based on Kenneth L. Pike's Tagmemic theory. This research was a qualitative and descriptive study, with the primary data source were the novel Mā Lā Nabūh Bih by Sandra Serag. Each type of complex sentence was selected and described according to Tagmemic theory. The results of this study found that four ‘harf’ functions were used as subordinating conjunctions based on the formation of the clauses, which consists of the arrangement of musnad (subject), musnad ilaih (predicate), and maf'ul bih (object). The distinguishes among four ‘harf’ functions are in the form and position of the subordinating conjunctions that separate the main sentence and its subordinate clauses, namely time relations (mundzu/since), causal relationship (lianna/because), complementary relationships (anna/really), comparative relationship (kaanna/as if). Complex sentences in the Tagmemic perspective are more complex than other types of sentence structures since they may consist of two slots, two classes, two roles, or two cohesions. In contrast, other sentence structure types have only one slot, class, role, and cohesion.